The 1st Baltic Osseointegration Academy and Lithuanian University of Health Sciences Consensus Conference 2016. Summary and Consensus Statements: Group I - Peri-Implantitis Aetiology, Risk Factors and Pathogenesis - Claudio Stacchi; Mindaugas Pranskunas; Lukas Poskevicius; Gintaras Juodzbalys; Ricardas Kubilius; Ryo Jimbo; Federico Berton; Giuseppe Perinetti; Andrea Frassetto; Teresa Lombardi; Aiman Khoury; Francesca Andolsek; et al. (eJournal of Oral Maxillofacial Research)
Introduction: The task of Group 1 was to review and update the existing data concerning aetiology, risk factors and pathogenesis of peri-implantitis. Previous history of periodontitis, poor oral hygiene, smoking and presence of general diseases have been considered among the aetiological risk factors for the onset of peri-implant pathologies, while late dental implant failures are commonly associated with peri-implantitis and/or with the application of incorrect biomechanical forces. Special interest was paid to the bone cells dynamics as part of the pathogenesis of peri-implantitis.